2014
DOI: 10.4049/jimmunol.1400742
|View full text |Cite
|
Sign up to set email alerts
|

Altered Expression of Autoimmune Regulator in Infant Down Syndrome Thymus, a Possible Contributor to an Autoimmune Phenotype

Abstract: Down syndrome (DS), caused by trisomy of chromosome 21, is associated with immunological dysfunctions such as increased frequency of infections and autoimmune diseases. Patients with DS share clinical features, such as autoimmune manifestations and specific autoantibodies, with patients affected by autoimmune polyendocrine syndrome type 1. Autoimmune polyendocrine syndrome type 1 is caused by mutations in the autoimmune regulator (AIRE) gene, located on chromosome 21, which regulates the expression of tissue-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 43 publications
2
31
1
1
Order By: Relevance
“…§One or more positive titer for GADA, IA-2A, or ZnT8A. ||DS-PNDM vs. non-DS PNDM, P = 0.006. than those in the study by Skogberg et al (28) (2 months-12 years); therefore, a potential temporal relationship of AIRE expression in DS thymus, possibly linked to AIRE's role in differentiation and turnover of thymocytes (29,30), could explain the difference. None of the cases were reported to have diabetes; however, 11 of 19 reported by Giménez-Barcons et al had organ-specific autoimmunity (hypothyroidism, Graves disease, or celiac disease).…”
Section: Discussioncontrasting
confidence: 53%
“…§One or more positive titer for GADA, IA-2A, or ZnT8A. ||DS-PNDM vs. non-DS PNDM, P = 0.006. than those in the study by Skogberg et al (28) (2 months-12 years); therefore, a potential temporal relationship of AIRE expression in DS thymus, possibly linked to AIRE's role in differentiation and turnover of thymocytes (29,30), could explain the difference. None of the cases were reported to have diabetes; however, 11 of 19 reported by Giménez-Barcons et al had organ-specific autoimmunity (hypothyroidism, Graves disease, or celiac disease).…”
Section: Discussioncontrasting
confidence: 53%
“…Inactivating AIRE mutations lead to autoimmune polyendocrine syndrome type I (APS1), an autosomal recessive disease that shares specific autoantibodies with DS but different disease patterns. Hypoparathyroidism and Addison's disease, hallmarks of APS1, are extremely rare in DS patients, while Hashimoto's thyroiditis, Graves' disease (GD) and type 1 diabetes mellitus are the most typical DS-associated endocrine autoimmune diseases [10]. Contrasting data regarding thymic expression of AIRE in DS have been reported.…”
Section: Down's Syndromementioning
confidence: 99%
“…Exosomes are nano‐sized membrane enclosed vesicles of endocytic origin, and are released into the extracellular space by cells when multivesicular bodies fuse with the cell plasma membrane. Previous work have identified and characterized exosomes in murine 7 as well as human thymic tissue 8 , 9 . Unlike other human epithelial cell types 10 it is still however, not formally shown that the TEC population is able to produce these extracellular vesicles.…”
mentioning
confidence: 96%
“…Previous work have identified and characterized exosomes in murine 7 as well as human thymic tissue. 8,9 Unlike other human epithelial cell types 10 it is still however, not formally shown that the TEC population is able to produce these extracellular vesicles. Following the finding that B cells secrete antigen-presenting exosomes 11 several studies have shown exosomes to be capable of presenting antigens for T cells by themselves 12,13 or indirectly via uptake by dendritic cells (DCs).…”
mentioning
confidence: 99%